Serological surveillance of West Nile virus and molecular diagnostic of West Nile virus, Usutu virus, avian influenza and Newcastle disease virus in wild birds of Portugal - Costa, Ana Catarina de Almeida (2021)
Dissertação de Mestrado Integrado em Medicina Veterinária